Right-Wing Authoritarianism and Antipathy Toward Immigrants and Sexual Minorities in the Early Days of the Coronavirus Pandemic in Italy - Pacilli, Maria Giuseppina; Pagliaro, Stefano; Bochicchio, Vincenzo; Scandurra, Cristiano; Jost, John T. (Frontiers in Political Science, 2022)
Theory and research in social, evolutionary, and political psychology indicates that subjective feelings of threat and exposure to objectively threatening circumstances—including pandemic diseases—may contribute to increased affinities for political conservatism, right-wing authoritarianism, and antypathy toward immigrants and sexual minorities. We investigated these possibilities in the context of Italy, which was the first Western country to be severely affected by the spread of COVID-19. From March 3-8, 2020, we surveyed 757 adults ranging in age from 18 to 78 years. Results showed that antipathy toward immigrants and sexual minorities was predicted by (male) sex, COVID-19 anxiety, RWA, and political distrust. Furthermore, we observed that increasing COVID-19 anxiety magnified the effect of RWA on antipathy toward immigrants and sexual minorities. Implications for the theories of authoritarianism and political ideology as motivated social cognition, the importance of maintaining political trust when governments are forced to confront public health crises, and the state of contemporary Italian politics are discussed.